Effect of circulation and micro-aeration on sludge characteristics and microbial community in an ABR for treating traditional Chinese medicine wastewater. Issue 25 (9th November 2020) - Su, Chengyuan; Deng, Qiujin; Lu, Yuxiang; Pan, Jiaqi; Chen, Wuyang; Chen, Shenglong; Deng, Xue; Lin, Xiangfeng; Huang, Zhi
ABSTRACT: The effects of circulation reflux and micro-aeration on the performance of a modified anaerobic baffled reactor (ABR) for treatment of traditional Chinese medicine (TCM) wastewater were evaluated. The characteristics of anaerobic sludge and microbial community structure in the modified ABR were also investigated. The results indicated that with conditions of reflux ratio of 1, reflux ratio of 2, reflux ratio of 2 with micro-aeration, and reflux ratio of 3, the modified ABR achieved an average COD removal efficiency of 90%, 87.7%, 87.8%, and 88.4%, respectively. In addition, the NH3 -N average removal efficiency was 45.1%, 50%, 55.9%, and 55.4%, respectively. The analysis of excitation–emission matrix (EEM) fluorescence spectra of soluble microbial products (SMP) and extracellular polymeric substances (EPS) showed that there were tyrosine-like, aromatic protein-like, and coenzyme F420 substances in the sludge. The EPS were analysed by the Fourier transform infrared spectroscopy (FTIR), which showed that aromatic compounds were partially degraded, while the protein and polysaccharide compounds increased in each compartment of the modified ABR. Interestingly, the microbial community of anaerobic sludge analysis results showed that Chloroflexi was the dominant in the first, third and fourth compartments. Meanwhile, Levilinea and Methanothrix were the dominant species in the first and third compartments at the genus level. GRAPHICAL ABSTRACT: UF0001